The great importance of normalization of LC–MS data for highly‐accurate non‐targeted metabolomics. (16th November 2016) - Mizuno, Hajime; Ueda, Kazuki; Kobayashi, Yuta; Tsuyama, Naohiro; Todoroki, Kenichiro; Min, Jun Zhe; Toyo'oka, Toshimasa
Abstract: The non‐targeted metabolomics analysis of biological samples is very important to understand biological functions and diseases. LC combined with electrospray ionization‐based MS has been a powerful tool and widely used for metabolomic analyses. However, the ionization efficiency of electrospray ionization fluctuates for various unexpected reasons such as matrix effects and intraday variations of the instrument performances. To remove these fluctuations, normalization methods have been developed. Such techniques include increasing the sensitivity, separating co‐eluting components and normalizing the ionization efficiencies. Normalization techniques allow simultaneously correcting of the ionization efficiencies of the detected metabolite peaks and achieving quantitative non‐targeted metabolomics. In this review paper, we focused on these normalization methods for non‐targeted metabolomics by LC–MS.